Supported Single Atoms as New Class of Catalysts for Electrochemical Reduction of Carbon Dioxide. Issue 9 (28th February 2019) - Cheng, Yi; Yang, Shize; Jiang, San Ping; Wang, Shuangyin
Abstract: Carbon dioxide (CO2 ) emitted from excess consumption of fossil fuels leads to the rise of CO2 concentrations in the atmosphere. One of the most attractive solutions to cut CO2 emission is the electrochemical reduction of CO2 to produce fuels and build a low carbon emission economy. However, the electrochemical CO2 reduction reaction (CO2 RR) is a great challenge due to the activation of the highly stable, linear CO2 molecules, and the process involves proton‐coupled multi‐electron transfer with a high energy barrier. Thus, it is critical to develop efficient and highly stable catalyst materials for CO2 RR. Nanoparticle‐based electrocatalysts have been extensively investigated, but the broad size distribution not only limits their activity due to the size‐dependent catalytic properties, but also constrains the selectivity and leads to undesired side reactions. Single‐atom catalysts (SACs), a rising star in the catalytic area, can combine the merits of heterogeneous and homogeneous catalysts, offering outstanding opportunities for CO2 RR. The advent of SACs for CO2 RR has attracted enormous attention recently, and great effort has been devoted into the area and significant advancements have been achieved in recent years. Here, this mini review updates the development of SACs for CO2 RR, and their opportunities and challenges are discussed. Abstract : The climate change urges human beings to cut down carbon dioxide (CO2 ) emission immediately. Electrochemical reduction of CO2 (CO2 RR) to produce fuels provides a promising option for CO2 utilization and renewable energy storage. Electrocatalysts are the key to achieve highly efficient CO2 RR, and the newly developed supported single‐atom catalysts offer new opportunities to convert CO2 to fuels.